2017
DOI: 10.1371/journal.pone.0171999
|View full text |Cite
|
Sign up to set email alerts
|

Long-term renal outcomes in patients with traumatic brain injury: A nationwide population-based cohort study

Abstract: BackgroundTraumatic brain injury (TBI) is an important cause of death and disability worldwide. The relationship between TBI and kidney diseases is largely unknown.MethodsWe aimed to determine whether TBI is associated with long-term adverse renal outcomes. We performed a nationwide, population-based, propensity score-matched cohort study of 32,152 TBI patients and 128,608 propensity score-matched controls. Data were collected by the National Health Insurance Research Database of Taiwan from 2000 to 2012. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 30 publications
(32 reference statements)
1
19
0
Order By: Relevance
“…Our previous cohort study reported a substantial correlation between stroke and higher risks for CKD, a decline in the renal function, and ESRD . In the similar long‐term cohort study, we also reported that both migraine and traumatic brain injury are independent risk factors for CKD or ESRD . Perhaps, the interaction between these neuropeptides and CKD is mediated by the activation of renal sympathoexcitation via vaso‐afferent nerve activation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous cohort study reported a substantial correlation between stroke and higher risks for CKD, a decline in the renal function, and ESRD . In the similar long‐term cohort study, we also reported that both migraine and traumatic brain injury are independent risk factors for CKD or ESRD . Perhaps, the interaction between these neuropeptides and CKD is mediated by the activation of renal sympathoexcitation via vaso‐afferent nerve activation …”
mentioning
confidence: 99%
“…10 In the similar long-term cohort study, we also reported that both migraine and traumatic brain injury are independent risk factors for CKD or ESRD. 11,12 Perhaps, the interaction between these neuropeptides and CKD is mediated by the activation of renal sympathoexcitation via vaso-afferent nerve activation. 13,14 Most patients who present with acute ischemic stroke to the emergency department are hypertensive.…”
mentioning
confidence: 99%
“…A nationwide populationbased cohort study in Taiwan reported that TBI increased the incidence of CKD. 62 AKI is associated with the small-vessel damage in both the brain and kidneys that can result in ischemia. Since AKI is an inflammatory condition, increased inflammatory cytokines and thrombin generation can exacerbate secondary damage after TBI.…”
Section: Organ System Dysfunction In Tbimentioning
confidence: 99%
“…The primary outcome was incident CKD defined by at least three ICD-9-CM codes for at least 3 months (Supplemental Table 1) (12)(13)(14)(15). Potential relevant confounding variables included demographics, important comorbidities identified by at least three diagnosis codes within 1 year before rheumatoid arthritis diagnosis (Supplemental Table 1), and long-term medications, such as antidiabetic drugs, diuretics, angiotensin-converting enzyme inhibitors or angiotensin II receptor blockers, and nonsteroidal antiinflammatory drugs (NSAIDs).…”
Section: Outcomes and Relevant Variablesmentioning
confidence: 99%